As a Cause of Fever Unknown Origin, Waldenstrom's Macroglobulinemia: a Case Report - mehmet ozen; Ibrahim Haznedaroğlu (Mediterranean Journal of Hematology and Infectious Diseases)
Introduction: Waldenstrom's macroglobulinemia is a B cell lymphoplasmacytoid lymphoma. However, Waldenstrom's macroglobulinemia is not considered as a cause of fever unknown origin.